PERANCANGAN FLIPBOOK DIGITAL INTERAKTIF DENGAN CHATBOT EDUKATIF PADA MATERI RANTAI MAKANAN UNTUK SISWA SEKOLAH DASAR - Dina Rahmadani; Sarini Vita Dewi (Badan Penelitian dan Pengabdian Masyarakat (BP2M) STMIK Syaikh Zainuddin NW Anjani, 2026)
The advancement of digital technology demands the presence of innovative learning media that can support interactive and engaging learning processes, especially at the elementary school level. One of the materials that requires visualization support and good conceptual understanding is the food chain material in the Natural and Social Sciences (IPAS) subject. This study aims to design and develop learning media in the form of an interactive digital flipbook equipped with a simple educational chatbot on the food chain material for elementary school students. The research method used is the Research and Development (R&D) method by applying the ADDIE model which is limited to the analysis, design, and development stages. The developed media was then validated by two media experts and two material experts using an assessment instrument in the form of a questionnaire. The validation results showed that the flipbook learning media with an educational chatbot obtained a feasibility percentage of 93.3% from the media experts and 97.3% from the material experts, which is categorized as very feasible. Based on these results, the developed learning media is considered suitable for use as an alternative media in learning the food chain. It is hoped that this research can be a reference or reference material in the development of interactive digital learning media in elementary schools.